Review of Intravenous Acetaminophen for Analgesia in the Postoperative Setting. Issue 11 (November 2021) - Tompkins, Danielle M.; DiPasquale, Arielle; Segovia, Michelle; Cohn, Stephen M.
Background: Acetaminophen is a non-opioid analgesic commonly utilized for pain control after several types of surgical procedures. Methods: This scoping primary literature review provides recommendations for intravenous (IV) acetaminophen use based on type of surgery. Results: Intravenous acetaminophen has been widely studied for postoperative pain control and has been compared to other agents such as NSAIDs, opioids, oral/rectal acetaminophen, and placebo. Some of the procedures studied include abdominal, gynecologic, orthopedic, neurosurgical, cardiac, renal, and genitourinary surgeries. Results of these studies have been conflicting and largely have not shown consistent clinical benefit. Conclusion: Overall, findings from this review did not support the notion that IV acetaminophen has significant efficacy for postoperative analgesia. Given the limited clinical benefit of IV acetaminophen, especially when compared to the oral or rectal formulations, use is generally not justifiable.